Induction of an Antibody Response against Plasmodium falciparum F2RIIEBA by Heterologous Prime-boost Immunisation - Rapeah Suppian; Norazmi Mohd Nor (Tropical Life Sciences Research, 2013)
Heterologous prime-boost immunisation strategies can evoke powerful antibody responses and may be of value in developing an improved malaria vaccine. Herein, we show that an immunisation protocol that primes Balb/c mice with a recombinant Bacille Calmette-Guérin (rBCG) vaccine consisting of a plasmid encoding a synthetic fragment of the ESAT-6 epitope of Mycobacterium tuberculosis, the fragment 2 region II of erythrocyte-binding antigen (F2RIIEBA) and the three repeat sequences of the circumsporozoite protein (NANP)3 of Plasmodium falciparum before subsequently boosting the mice with either two doses of the rBCG clone or with a DNA vaccine expressing the native form of F2RIIEBA generating higher serum anti-F2RIIEBA antibody levels than an immunisation protocol that calls for a homologous prime-boost with two doses of rBCG. These results demonstrate the potential of DNA vaccination in boosting the antibody response to a recombinant vaccine expressing multiple epitopes. Heterologous prime-boost immunisation strategies can evoke powerful antibody responses and may be of value in developing an improved malaria vaccine. Herein, we show that an immunisation protocol that primes Balb/c mice with a recombinant Bacille Calmette-Guérin (rBCG) vaccine consisting of a plasmid encoding a synthetic fragment of the ESAT-6 epitope of Mycobacterium tuberculosis, the fragment 2 region II of erythrocyte-binding antigen (F2RIIEBA) and the three repeat sequences of the circumsporozoite protein (NANP)3 of Plasmodium falciparum before subsequently boosting the mice with either two doses of the rBCG clone or with a DNA vaccine expressing the native form of F2RIIEBA generating higher serum anti-F2RIIEBA antibody levels than an immunisation protocol that calls for a homologous prime-boost with two doses of rBCG. These results demonstrate the potential of DNA vaccination in boosting the antibody response to a recombinant vaccine expressing multiple epitopes. Strategi imunisasi prime-boost secara heterologus boleh merangsang gerak balas antibodi yang lebih berkesan dan mungkin penting dalam pembangunan vaksin malaria yang lebih baik. Dalam kajian ini, kami telah menunjukkan bahawa imunisasi mencit Balb/c dengan vaksin Bacille Calmette-Guerin rekombinan (rBCG) yang mengandungi plasmid yang mengekodkan fragmen sintetik epitop ESAT-6 Mycobacterium tuberculosis, fragmen 2 kawasan II antigen pengikat eritrosit (F2RIIEBA) dan tiga jujukan berulang protein circumsporozoite (NANP)3 Plasmodium falciparum sebelum diberikan dos penggalak, sama ada dua dos klon rBCG atau vaksin DNA yang mengekspreskan F2RIIEBA natif, menghasilkan paras antibodi anti-F2RIIEBA yang lebih tinggi dalam serum berbanding dengan kaedah imunisasi secara homologous menggunakan dua dos rBCG. Keputusan ini menunjukkan potensi vaksinasi vaksin DNA dalam merangsang gerak balas antibodi terhadap vaksin rekombinan yang mengekspreskan beberapa epitop.